2020
DOI: 10.1186/s12875-020-01119-8
|View full text |Cite
|
Sign up to set email alerts
|

Promoting rational antibiotic prescribing for non-complicated infections: understanding social influence in primary care networks in Germany

Abstract: Background: Primary care networks in Germany are formalized regional collaborations of physicians and other healthcare providers. Common goals are optimized healthcare processes and services for patients, enhanced communication, agency for professional concerns and strengthened economic power. In the ARena study (Sustainable reduction of antibiotic-induced antimicrobial resistance), 14 primary care networks in two federal German states aimed to promote appropriate antibiotics use for acute non-complicated infe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 33 publications
(47 reference statements)
3
19
0
Order By: Relevance
“…Aiming to foster appropriate antibiotic prescribing for respiratory tract infections during ambulatory visits, the authors identified a decrease of inappropriate prescription rates from 19.9% to 3.7% in 18 months attributable to peer comparison mechanisms. Such peer mechanisms and social influences have been identified in ARena as well [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aiming to foster appropriate antibiotic prescribing for respiratory tract infections during ambulatory visits, the authors identified a decrease of inappropriate prescription rates from 19.9% to 3.7% in 18 months attributable to peer comparison mechanisms. Such peer mechanisms and social influences have been identified in ARena as well [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the PCNs were expected to be an enabling factor for change of prescribing routines. This was also supported by process evaluation findings [20,25] which confirmed that it was an appropriate choice to conduct the ARena trial in the setting of PCNs. Observed antibiotic prescribing in the intervention arms at baseline [26] was both, lower than expected and lower than in matched standard care.…”
Section: Discussionmentioning
confidence: 53%
“…Response rates were 75.5% (T0 n = 229), 64.0% (T1 n = 200) and 63.3% (T2 n = 184) [ 21 ]. At time of T0, 148 (55.0%) of all responders were male and the average age was 54.0 years (SD 7.6).…”
Section: Resultsmentioning
confidence: 99%
“…A qualitative study within the process evaluation of ARena pointed in the same direction [ 21 ]: Physicians described PCNs as supportive with regard to exchange (beliefs, ideas and experiences), management, and the implementation of new routines in practice, which can influence decision-making on antibiotic prescribing [ 21 , 29 ]. Research further showed that PCNs can act as effective drivers of innovation and quality improvement, especially when communication and support functioned well within the networks [ 21 , 30 , 31 ]. Being part of a PCN can thus support the adoption of specific behaviors and beliefs [ 13 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation